Contagious Diseases, Faith, Superstitions and the Cult of Saint Charalambos - Pilipović, Radovan (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
From the first half of the 16th century and almost until the middle of the 19th century, the area of ​​the Balkan Peninsula, inhabited by Serbs, was hit by waves of deadly infections, most often of the plague type. Great mortality and epiphenomena of disease: fear, mutilation, loss of loved ones affected the socio-religious construct, placing the Church in a horizontal social plane and confronting it with special challenges in the process of its missionary work. The sought-after protection from the effects of infections, a pronounced prayerfulness and emphasized forms of piety also influenced the formation of cults of saints. The cult of St. Charalambos, an early Christian martyr from the 3rd century, as a protector against plague and infections, whose mediation was invoked and additionally encouraged the picturesque world of ideas created from dogmatic and liturgical texts and corresponding forms of behavior.
Keywords: diseases; prirodne katastrofe; famine; astronomical phenomena; protective power of the saint's cult; St. Charalambos